STRATEGI PELATIHAN SUMBER DAYA MANUSIA UNTUK KEBUTUHAN MD. ANIMATION (Studi Kasus Strategi Pelatihan di GMC Animation Solo) - Winoto, Sugiyo (Jurnal Ilmiah Multimedia dan Komunikasi, 2018)
The role of animation education, especially for the production process learning, in vocational and higher education institution is considered still lacking, because the animation curriculum is too general, since all knowledge of animation production is taught, and at the end students must be able to master all areas of animation. In fact, the animation industry needs creative people who have certain skills and special abilities (animating, modeling, rigging, background artist, texturing). MD Animation, a subsidiary of MD Entertainment collaborates with the GMC Animation Solo Studio to recruit qualified animators. GMC Animation Solo organizes training / courses for prospective animators. This study examines the strategies of human resources training for the needs of MD Animation. The research methods used were case study and descriptive analysis. The training strategy undertaken by GMC Animation Solo is in the form of training material referring to the needs of MD Animation. Participants are trained to work on animation products by imitating examples from the existing animation products, both domestic and foreign products. Since its establishment in 2013 until now the GMC Animation Solo has only been able to supply 66 people to MD Animation. While the animators needs for Adit, Sopo & Jarwo’s film production are for about 350 animators. The obstacles faced by GMC Animation Solo among others are the lack of infrastructure, it has not been managed professionally, and the lack of experienced instructors. For further research it is recommended that the results of this study can be the initial information and then similar researchers can find solutions for the GMC Animation to be better developed.